EXCAVATIONS OF MOUND 1 NEAR THE VLG. KOMYSHUVAKHA, DONETSK REGION IN 2017 - Бровендер, Юрій; Русінов, Андрій (SWorldJournal, 2024)
The article is devoted to the results of archaeological excavations of mound 1 near the village of Komyshuvakha on the territory of the Kramatorsk City Council of Donetsk region, conducted in 2017. Materials from burials of the Dnieper-Don Babyn culture